LEGAL REGULATION OF DIGITAL ECONOMY IN EU AND IMPLEMENTATION OF EU EXPERIENCE IN UZBEKISTAN (Conferencea, 2022)
A digital economy is a transformed form of an economy where all the activities are done by using modern technology to enhance the outcomes. The regulations for maintaining the rule of law in this prospective domain have gotten more significant with the passage of time and with the rise of new technology. This paper analyses the digital law and regulation of the digital economy in the European Union. The outcome of the research provides a way for developing countries to align their legislation with the modern world.